Enhancing Employee Performance through Organizational Citizenship Behavior and Quality of Work Life - Endang Sugiarti (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Employee performance in Indonesia’s energy sector faces challenges from heavy workloads, shifting organizational cultures, and limited work–life balance, making it essential to examine the roles of organizational citizenship behavior and quality of work life as key drivers of productivity and sustainability. This study investigates the influence of organizational citizenship behavior and quality of work life on employee performance. The research was conducted using a quantitative method with a sample of 258 employees. Data were collected through structured questionnaires and analyzed using Structural Equation Modelling (SEM) via AMOS. The demographic analysis revealed that the majority of respondents were male, aged between 31–40 years, and held a Bachelor’s degree. The results confirmed that organizational citizenship behavior had a significant positive effect on employee performance, indicating that voluntary behaviors beyond formal roles contribute meaningfully to work outcomes. Likewise, quality of work life also had a significant positive impact, showing that aspects such as work–life balance and supportive work environments are essential for optimal performance. Both variables were discussed based on their behavioral and organizational implications. The findings underline the importance of fostering a conducive work environment and encouraging extra-role behaviors to enhance employee productivity in corporate settings.